Nitrogen Mineralisation in a Clonal Eucalyptus Plantation on Sandy Soil After Clearfelling and Residue Burning - Dovey, S. B.; Du Toit, B. (Indian Forester, 2015)
A study was designed to compare in situ soil N fluxes in a clonal Eucalyptus plantation (mean annual increment 21 m3 ha-1 at 7 years) on sandy low-N soils. The study was established in an undisturbed eucalypt and clearfelled eucalyptus plantation. Clearfelled plots were subjected to residue burning (Burn) and residue retention (No-burn) prior to reestablishment. A sequential open and closed soil coring method was used to determine cumulative N-mineralisation, surface leaching and root uptake fluxes in the top 0 to 30 cm soil layer. Mineralisation and immobilisation in the undisturbed forest remained near zero over the study period, accumulating as net N immobilisation. Clearfelling increased net N mineralisation and nitrification, increasing mobile NO3-N concentrations in the surface soil. Surface N leaching was increased and root uptake decreased after clearfelling. Surface N leaching was not altered by residue burning. Net N mineralisation in the burn plots was less than in the no-burn plots, reduced after burning by nearly 53% over the 20.1 monthperiod. Atmospheric inputs strongly contributed to N inputs across all treatments.